Modeling Design of Picohydro Power Generation System Using Crossflow Turbine - Apriani, Yosi; Hidayat, Syarif; Saleh, Zulkiffli; Oktaviani, Wiwin A; Mochamad Sofian, Ian (PT FORMOSA CENDEKIA GLOBAL, 2024)
The goal of this project is to learn how to use a Crossflow turbine to create a Picohydro power plant system modeling. The manufacturing process, from design to evaluation, is the methodology employed. The turbine type utilized is a crossflow turbine, measuring 26 cm in outer diameter, 17.3 cm in inner diameter of the blade runner, and up to 35 pieces of blades. The calculations show that the distance between the blades is 2.3 cm, the blade length is 8.5 cm, the blade width is 4.4 cm, and the radius of curvature of the blade is 2.8 cm. The test results without load obtained the highest turbine rotation of 421 Rpm produces a voltage of 7.29 V before going through the boost converter.